FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN BALITA GIZI BURUK (SKOR Z BB/U < -3) DI KABUPATEN WONOGIRI TAHUN 2017 - Suci Nurraini; Suyatno Suyatno; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2018)
Malnutrition (W/A) is still one of the health problems in Indonesia and the most vulnerable age group suffering from malnutrition is children under five years old. In 2013, the national prevalence of malnutrition-less in children under five is 19.6%, which means malnutrition-less problems in Indonesia are still a public health problem. The number of malnutrition cases in Wonogiri District in 2016 were 158 cases. The purpose of this study is to determine the risk factors associated with the incidence of malnutrition children under five in Wonogiri District. This type of research is an analytical survey with case control study design. The case group is children under five with Z-Score <-3 while the control group is children under five with Z-Score <-3 SD based on the W/A index. The sample was 34 for each group selected by purposive sampling technique. The result showed that there was significant correlation between malnutrition and infectious disease (p=0,011), parenting (p=0,011), maternal education level (p=0,002;) knowledge of mother (p=0,002), mother attitude level (p=0,012), mother practice level (p=0,011) and family economic status (p=0,039). There was no significant correlation between malnutrition and sex (p=1,000), age (p=0,334), energy sufficiency (p=0,582), protein adequacy level (p=0,742), and mother work status (p=0,123). It can be concluded that risk factors associated with the incidence of malnutrition in Wonogiri District are infectious diseases; parenting; mother's education level; level of knowledge, attitude, and practice of mother; and family economic status. Health workers are advised to always give information to society so that mother’s knowledge about baby nutrition increase.